Cell surface tetraspanin Tspan8 contributes to molecular pathways of exosome-induced endothelial cell activation - Nazarenko, Irina; Rana, Sanyukta; Baumann, Alexandra; McAlear, Jessica; Hellwig, Andrea; Trendelenburg, Michael; Lochnit, Günter; Preissner, Klaus T.; Zöller, Margot (Cancer research)
Tumor-derived exosomes containing the tetraspanin Tspan8 can efficiently induce angiogenesis in tumors and tumor-free tissues. However, little information exists on exosome-endothelial cell (EC) interactions or the proangiogenic role of tetraspanins, which are a constitutive component of exosomes. In this study, we used a rat adenocarcinoma model (AS-Tspan8) to explore the effects of exosomal Tspan8 on angiogenesis. Tspan8 contributed to a selective recruitment of proteins and mRNA into exosomes, including CD106 and CD49d, which were implicated in exosome-EC binding and EC internalization. We found that EC internalized Tspan8-CD49d complex-containing exosomes. Exosome uptake induced vascular endothelial growth factor (VEGF)-independent regulation of several angiogenesis-related genes, including von Willebrand factor, Tspan8, chemokines CXCL5 and MIF, chemokine receptor CCR1, and, together with VEGF, VEGF receptor 2. EC uptake of Tspan8-CD49d complex-containing exosomes was accompanied by enhanced EC proliferation, migration, sprouting, and maturation of EC progenitors. Unraveling these new pathways of exosome-initiated EC regulation could provide new options for therapeutic interference with tumor-induced angiogenesis. Cancer Res; 70(4); 1668-78